Lemma 40.5.1. The map $I/I^2 \to J/J^2$ induced by $c$ is the composition

where the second arrow comes from the equality $J = (I \otimes B + B \otimes I)C$. The map $i : B \to B$ induces the map $-1 : I/I^2 \to I/I^2$.

Let $S$ be a scheme. Let $(U, R, s, t, c, e, i)$ be a groupoid scheme over $S$. Let $u \in U$ be a point. In this section we explain what kind of structure we obtain on the local rings

\[ A = \mathcal{O}_{U, u} \quad \text{and}\quad B = \mathcal{O}_{R, e(u)} \]

The convention we will use is to denote the local ring homomorphisms induced by the morphisms $s, t, c, e, i$ by the corresponding letters. In particular we have a commutative diagram

\[ \xymatrix{ A \ar[rd]_ t \ar[rrd]^1 \\ & B \ar[r]^ e & A \\ A \ar[ru]^ s \ar[rru]_1 } \]

of local rings. Thus if $I \subset B$ denotes the kernel of $e : B \to A$, then $B = s(A) \oplus I = t(A) \oplus I$. Let us denote

\[ C = \mathcal{O}_{R \times _{s, U, t} R, (e(u), e(u))} \]

Then we have

\[ C = (B \otimes _{s, A, t} B)_{\mathfrak m_ B \otimes B + B \otimes \mathfrak m_ B} \]

Let $J \subset C$ be the ideal of $C$ generated by $I \otimes B + B \otimes I$. Then $J$ is also the kernel of the local ring homomorphism

\[ (e, e) : C \longrightarrow A \]

The composition law $c : R \times _{s, U, t} R \to R$ corresponds to a ring map

\[ c : B \longrightarrow C \]

sending $I$ into $J$.

Lemma 40.5.1. The map $I/I^2 \to J/J^2$ induced by $c$ is the composition

\[ I/I^2 \xrightarrow {(1, 1)} I/I^2 \oplus I/I^2 \to J/J^2 \]

where the second arrow comes from the equality $J = (I \otimes B + B \otimes I)C$. The map $i : B \to B$ induces the map $-1 : I/I^2 \to I/I^2$.

**Proof.**
To describe a local homomorphism from $C$ to another local ring it is enough to say what happens to elements of the form $b_1 \otimes b_2$. Keeping this in mind we have the two canonical maps

\[ e_2 : C \to B,\ b_1 \otimes b_2 \mapsto b_1s(e(b_2)),\quad e_1 : C \to B,\ b_1 \otimes b_2 \mapsto t(e(b_1))b_2 \]

corresponding to the embeddings $R \to R \times _{s, U, t} R$ given by $r \mapsto (r, e(s(r)))$ and $r \mapsto (e(t(r)), r)$. These maps define maps $J/J^2 \to I/I^2$ which jointly give an inverse to the map $I/I^2 \oplus I/I^2 \to J/J^2$ of the lemma. Thus to prove statement we only have to show that $e_1 \circ c : B \to B$ and $e_2 \circ c : B \to B$ are the identity maps. This follows from the fact that both compositions $R \to R \times _{s, U, t} R \to R$ are identities.

The statement on $i$ follows from the statement on $c$ and the fact that $c \circ (1, i) = e \circ t$. Some details omitted. $\square$

Your email address will not be published. Required fields are marked.

In your comment you can use Markdown and LaTeX style mathematics (enclose it like `$\pi$`

). A preview option is available if you wish to see how it works out (just click on the eye in the toolbar).

Unfortunately JavaScript is disabled in your browser, so the comment preview function will not work.

All contributions are licensed under the GNU Free Documentation License.

## Comments (0)